Ex-professional association footballers have an increased prevalence of osteoarthritis of the hip compared with age matched controls despite not having sustained notable hip injuries - Shepard, G. J.; Banks, A. J.; Ryan, W. G. (British Journal of Sports Medicine, 2003)
Objective: To compare the prevalence of self reported, physician diagnosed osteoarthritis (OA) of the hip in ex-professional footballers with that in age matched controls in the general public. Method: A questionnaire was sent to the 92 football league and premiership managers to assess the prevalence of OA of various joints. The prevalence of OA of the hip in those managers that were ex-professional footballers was assessed. Radiographic controls were obtained and used to assess the prevalence of OA of the hip in the general population. The results of the two groups were compared statistically using 2 tabulation. Results: Seventy four (80%) of the managers responded to the questionnaire. Nine of the 68 ex-professional footballers who replied had OA of the hip, and six of these had undergone a total of eight total hip replacements. Of the 18 managers who did not respond, 12 were known to be ex-professionals. In the control group of 136, two had OA of the hip. The two groups differed significantly (p<0.001). The odds ratio for OA of the hip was 10.2 (95% confidence interval 2.1 to 48.8). Conclusion: The ex-professional footballers had a significantly higher prevalence of OA of the hip than an age matched group of radiographic controls.